Creeds, Body, Institution and the Use of Technological Devices in the Resistance Work of Marta María Pérez Bravo - Ravelo García, Mónica R.; Cárdenas Castro, Álvaro A.; Villanueva Donoso, Jaime (Eikón / Imago, 2022)
In this article, we analyze a set of works by the Cuban- Mexican artist Marta María Pérez Bravo and we systematize her work in general based on thematic, aesthetic, and technical developments over time. We apply the perspective of the Resistance Art, the qualitative methodology, and the method of Analysis of Discourse. We analyze different issues embedded in Perez Bravo’s work, which validate it as a critical or resistance art placed, above all, in Cuba. Some expressions of it are that she transforms the current aesthetic paradigms; reelaborates historically discriminated religious practices; questions the construction of gender in Cuba and the unequal participation of women in religious practices and the society; exposes political and social problems such as freedom of expression and clandestine practices of economic survival. At the same time, we note the ontological, artistic, and political meanings of the use of technical devices to capture images, both in photography and video, in the passing from analog to digital variants.